(untitled) (Research, Society and Development, 2021)
The generation of polymeric waste has three aspects: the increasing volume, complexity and environmental pollution. Recycling comes with the aim of reducing the amount of these residues generated, consisting of a process of transformation of materials, previously separated, in order to allow their recovery. In the current situation, biological degradation through biodegradable polymers is considered the new sustainable trend. Biodegradable polymers compared to synthetic polymers degrade in less time due to the action of microorganisms, having properties similar to each other. This work aims to describe the biological degradation of polymeric materials, taking into account natural and synthetic biodegradable polymers. In general, natural biodegradable polymers have a high rate of renewability and can be used both in medical and environmental areas, since after disposal they are biodegraded by microorganisms present in the environment, in a short time compared with traditional polymeric materials. Synthetic biodegradable polymers have been more widely used in biomedical applications because they present excellent mechanical resistance, bioabsorbable, biocompatibility, biodegradability, non-toxicity, flexibility and, moreover, are applied in special packaging.